Plagues, climate change, and the end of an empire: A response to Kyle Harper's The Fate of Rome (1): Climate - Haldon, John F. (History compass, 2018)
Kyle Harper's The Fate of Rome, written for a popular audience, uses the environment to explain the decline and fall of the Roman Empire. The book asserts that Rome fell as a result of environmental stress, in particular through a combination of pandemic disease and climate change. Although we agree that the environment can and should be integrated within traditional historical accounts, we challenge the book's claims on several issues. These include Harper's use of primary sources and secondary literature, his approach to analyzing palaeoclimate data, his interpretations of the impact of disease on the Roman state and society, and his synthesis of social, economic, and environmental history. Throughout this and the following two sections of this review, we demonstrate that several major flaws undermine the book's overarching argument, casting serious doubts on its conclusions.